Jairo Varela, Carlos Molina y El Cachafaz: o la composición musical, fotográfica y bailable de la salsa - Merchán Mosquera, Silvia Fernanda (Universidad de San Buenaventura, Cali, 2018)
This work, shows stories of the childhood of these characters: Carlos Molina "The world photographer of salsa" and Master Jairo Varela Martinez.In the first part of the work, the story "A photographer of heart born in the Barrio Obrero of Cali, Colombia" is presented, a history of the childhood of the character Carlos Molina "The World photographer of the Salsa", Jairo Varela Martinez, the cultural inheritance of his native town, and the Colombian Cachafaz a character with seven arts, he will say: dancer, composer, singer, phonymic, animator, declamador, poet... and crazy.....